2016
DOI: 10.1002/phar.1776
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing: An Application to Medication Management in Older Adults

Abstract: Polypharmacy has been found to have potentially negative consequences for patients due to use of potentially inappropriate medications, as well as increased risk of drug interactions and adverse effects. Deprescribing has been proposed as a method of improving medication use throughout a patient's course of care. This article reviews the process of deprescribing and applies the process to medication classes commonly encountered by clinical pharmacists. This review of therapeutics included studies identified th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Instead, comprehensive deprescribing interventions should be applied to target patients (such as male patients and old patients) or physicians (such as internists) in high-risk groups for utilizing or prescribing problematic polypharmacy. Evidence has proved that approaches such as shared decision making between patients and healthcare providers; providing infrastructural support for the coordination and continuity of care ( Bemben, 2016 ), especially for multi-morbidity patients ( Duerden et al, 2013 ); and educational programs on deprescribing for physicians are effective in improving problematic polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, comprehensive deprescribing interventions should be applied to target patients (such as male patients and old patients) or physicians (such as internists) in high-risk groups for utilizing or prescribing problematic polypharmacy. Evidence has proved that approaches such as shared decision making between patients and healthcare providers; providing infrastructural support for the coordination and continuity of care ( Bemben, 2016 ), especially for multi-morbidity patients ( Duerden et al, 2013 ); and educational programs on deprescribing for physicians are effective in improving problematic polypharmacy.…”
Section: Discussionmentioning
confidence: 99%
“…These results are incongruent with current guidelines that suggest CHEIs should be discontinued in severe dementia or at the end of life. 15,[18][19][20][21] The majority of patients in this study who were on a CHEI at time of admission did have a diagnosis of moderate dementia (58.3%) (where a CHEI is still indicated), however since their prognosis was estimated to be less than 3 months, there was a limited benefit of continuing their CHEI since they were close to the active stages of dying with a median length of stay of 21 days. These results corroborate with previous studies that show CHEIs are continued through the late stages of dementia and are not discontinued until the more active stages of dying.…”
Section: Discussionmentioning
confidence: 85%
“…18 CHEIs can be considered an unnecessary burden in the advanced stages of disease and many other studies corroborate with the University of Sydney's guidelines in suggesting that patients with end stage dementia should be discontinued on their CHEIs. [18][19][20][21] Unfortunately, studies have shown that individuals admitted to hospices or nursing homes with advanced dementia remain on CHEIs (20% at time of admission) or are tapered off CHEIs very close to their time of death. 22,23 Potential harms of continuing CHEIs in individuals with end stage dementia include drug interactions, cost of medication, pill burden, dysphagia, and a misunderstanding of a patient's goals of care.…”
Section: Introductionmentioning
confidence: 99%
“…20 The chances of polypharmacy greatly increase when several sets of guidance are being implemented in patients with multimorbidity 21 and healthcare professionals recognise that fulfilling multiple guidelines might compromise patient-centred care. 22 There is evidence this simultaneous medication administration can lead to an increased risk of patient hospitalisation 23 24 and work has begun to reduce this risk, 25 focusing on reducing inappropriate prescribing of non-steroidal anti-inflammatory drugs, proton pump inhibitors and duplicate therapy. 26 However progress is inconsistent and large interpractice variation in levels of polypharmacy remains.…”
Section: Introductionmentioning
confidence: 99%